Análisis comparativo de la productividad y distribución de fibra de alpaca entre Huancavelica y Puno - Crispin Cunya, Marianella (2009)
Alpaca fiber is one of the end products of the different types of rearing livestock, but the region is clearly recognized as alpaquera zone, whereby the sale of alpaca fiber is one of the permanent sources of income for these families Andes. However as knowledge of the alpaca fiber has low prices in the local market due to low levels of quality, the presence of intermediaries and a weak organization among some of the limiting factors.